Management of pulmonary vasodilator therapy in three pregnancies with pulmonary arterial hypertension. Issue 5 (14th February 2017) - Daimon, Atsushi; Kamiya, Chizuko A.; Iwanaga, Naoko; Ikeda, Tomoaki; Nakanishi, Norifumi; Yoshimatsu, Jun
Abstract: Pregnancy with pulmonary arterial hypertension (PAH) has a significantly high risk of maternal death and women with PAH are basically advised to avoid pregnancy. Recently, several reports have described pregnant women with PAH who were treated with pulmonary vasodilators during pregnancy and delivered safely. However, the efficacy of this treatment during pregnancy is still not clear. Here we report on the short‐term outcomes of three primiparous women with PAH who were prescribed pulmonary vasodilator therapy during their pregnancies. All women delivered preterm due to cardiac and/or obstetric reasons and were discharged without any complication. Pulmonary vasodilator therapy can be used safely during the pregnancies of PAH patients and may contribute to improved maternal and fetal prognoses.